The Aging GABAergic System and Its Nutritional Support - Demetra J. Mills (Journal of Nutrition and Metabolism)
Aging is associated with a decline in hormones and an associated decline in GABAergic function and calcium and ion current dysregulation. Neurosteroid hormones act as direct calcium channel blockers, or they can act indirectly on calcium channels through their interaction with GABA receptors. The calcium channel dysfunction associated with hormone loss further leads to an excitatory cell state, which can ultimately lead to cell death. The calcium theory of aging posits that cellular mechanisms, which maintain the homeostasis of cytosol Ca2+ concentration, play a key role in brain aging and that sustained changes in Ca2+ homeostasis provide the final common pathway for age-associated brain changes. There is a link between hormone loss and calcium dysregulation. Loss of calcium regulation associated with aging can lead to an excitatory cell state, primarily in the mitochondria and nerve cells, which can ultimately lead to cell death if not kept in check. A decline in GABAergic function can also be specifically tied to declines in progesterone, allopregnanolone, and DHEA levels associated with aging. This decline in GABAergic function associated with hormone loss ultimately affects GABAergic inhibition or excitement and calcium regulation throughout the body. In addition, declines in GABAergic function can also be tied to vitamin status and to toxic chemicals in the food supply. The decline in GABAergic function associated with aging has an effect on just about every body organ system. Nutritional support of the GABAergic system with supportive foods, vitamins, and GABA or similar GABA receptor ligands may address some of the GABAergic dysfunction associated with aging.